2005
DOI: 10.1086/426707
|View full text |Cite
|
Sign up to set email alerts
|

The Thermal Regulation of Gravitational Instabilities in Protoplanetary Disks. II. Extended Simulations with Varied Cooling Rates

Abstract: In order to investigate mass transport and planet formation by gravitational instabilities (GI's), we have extended our 3-D hydrodynamic simulations of protoplanetary disks from a previous paper. Our goal is to determine the asymptotic behavior of GI's and how it is affected by different constant cooling times. Initially, R disk = 40 AU, M disk = 0.07 M § , M * = 0.5 M § , and Q min = 1.8. Sustained cooling, with t cool = 2 orps (outer rotation periods, 1 orp ≈ 250 yrs), drives the disk to instability in ~ 4 o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
211
4

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 146 publications
(227 citation statements)
references
References 73 publications
(128 reference statements)
12
211
4
Order By: Relevance
“…On the other hand, as already mentioned, the outcome of gravitational instabilities in discs strongly depends on the assumptions about the disc thermal behaviour. Simulations that employ a cooling time constant with radius seem to show significant global energy transport (Mejia et al 2004), in contrast to our results. Of course, both a constant cooling timescale and our choice are highly idealized assumptions, and further studies are needed to assess which of the two is more reasonable.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…On the other hand, as already mentioned, the outcome of gravitational instabilities in discs strongly depends on the assumptions about the disc thermal behaviour. Simulations that employ a cooling time constant with radius seem to show significant global energy transport (Mejia et al 2004), in contrast to our results. Of course, both a constant cooling timescale and our choice are highly idealized assumptions, and further studies are needed to assess which of the two is more reasonable.…”
Section: Discussioncontrasting
confidence: 99%
“…In the case where M disc = 0.5M⋆ we observe the development of an initial transient m = 2 spiral structure, which induces a strong redistribution of matter and a steepening of the surface density profile, before the disc is eventually able to settle down as in the low disc mass case. Similar initial transients are also observed by Mejia et al (2004). We attribute it to an effect of the initial condition adopted.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Thermal processes play the primary role in regulating the amplitude and outcome of these instabilities (Pickett et al 1998(Pickett et al , 2000(Pickett et al , 2003Nelson et al 1998Nelson et al , 2000Mejía et al 2005). A disk's susceptibility to GIs can be parameterized by the Toomre Q-parameter (Toomre 1981); Q = c s κ/πGΣ, where c s is the sound speed, κ is the epicyclic frequency (∼ the rotation frequency Ω in a nearly Keplerian disk), and Σ is the disk surface mass density.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have shown that thermal physics controls GI amplitudes by a balance of heating and cooling (e.g., Tomley et al 1991Tomley et al , 1994Pickett et al 1998Pickett et al , 2000Pickett et al , 2003Gammie 2001;Boss 2002;Rice et al 2003;Mejía et al 2005;Boley et al 2006Boley et al , 2007aStamatellos & Whitworth 2008;Cossins et al 2009). Heating by GIs tends to increase c s , thus increasing Q.…”
Section: Introductionmentioning
confidence: 99%